MERANAP PEMBELAJARAN PENDIDIKAN LINGKUNGAN HIDUP DALAM KONFIGURASI PENDIDIKAN KEWARGANEGARAAN - Gunawati, Dewi (PKn Progresif, 2012)
This paper focuses on grounding learning environmental education in the configuration of civic education. The design of this study are expected to produce outputs in the form of an enlightened method of learning (technological humanists). In more systematically, this paper is to review studies that assessed environmental education in the two different approaches, namely the study of pedagogy and approaches to citizenship. Citizenship education as a cultural and educational character have cultural values ??and national character which include: religious, honest, tolerance, discipline, hard work, creative, independent, democratic, curiosity, semanga nationality, patriotism, respect for achievement, communicative , peace-loving, likes to read, care for the environment, social care and responsibility so as to explain the Life Education environment, implementation of environmental education studies as a preparation in a position themselves as good citizens.